Crafting Dexterity: Enhancing Fine Motor Skills in 4-5-Year-Olds through the Art of Paper Folding Origami - Innes, Risky Marlianka; Priyanti, Nita; Warmansyah, Jhoni; Yandira Siregar, Rahayu; Aribasoye, M.R. (Indonesian Journal of Early Childhood Educational Research (IJECER), 2023)
This study aims to assess the enhancement of fine motor skills through origami folding activities, employing Classroom Action Research (CAR). The research focuses on children aged 4-5 years (Group A) at Iqro Tuzrussa'adah Islamic Kindergarten, involving a total of 10 participants. Data collection utilizes observational methods, and the analysis employs quantitative descriptive techniques. The study unfolds over two cycles, and observation results indicate a noteworthy improvement in children's fine motor skills during origami paper folding activities, categorized as BSB. Pre-cycle results recorded 0% (no children), increasing to 20% (2 children) in Cycle I and further progressing to 50% (5 children) in Cycle II. These findings underscore the significance of fostering fine motor skills from an early age. Future research can explore diverse origami designs and consider longitudinal studies to understand the enduring impact on the development of fine motor skills. ┬áKeywords:┬á┬á